Mini‐Public's Statements and Media as Transmitters of Deliberative Judgments: A Field Experiment on a Citizens' Jury on Forest Policy - Leino, Mikko; Jäske, Maija; Setälä, Maija (Wiley, 2025)
Deliberative mini-publics have become commonplace in policymaking on complex issues such as climate policies. When assessing the macro-political impacts of deliberative mini-publics, it is important to examine how information about their procedures and outcomes is transmitted to the wider public. We conducted a field experiment to compare the effects of reading a mini-public statement to those of reading mediated information on a mini-public. Our experiment is based on a Citizens' Jury on forest use in Northern Finland, and it makes use of an actual piece from the media as well as an original mini-public statement. Using data collected from a panel of adults living in the region, we analyzed the effects that reading the statement or a newspaper article had on knowledge, policy support, perceived legitimacy, and efficacy in forest and climate change policy. Results show that reading the statement increased factual knowledge. Reading the news story covering the mini-public, in turn, had mixed impacts on factual knowledge. Furthermore, the news story seems to have reduced the perceived legitimacy of forest management, whereas the full statement had no effect on legitimacy beliefs. We conclude that the macro-political impacts of mini-publics depend on the type of media from which citizens receive information.